Pengaruh Kualitas Pelayanan dan Harga Terhadap Keputusan Pembelian di Indomaret - Sibarani, Maria Tresia (Jurnal Manajemen dan Administrasi Antartika, 2025)
Penelitian ini bertujuan untuk mengidentifikasi bagaimana kualitas pelayanan dan harga mempengaruhi keputusan pembelian di Indomaret Camar Raya Kranggan. Keputusan pembelian merupakan proses di mana individu memilih perilaku yang paling sesuai dari beberapa alternatif, dengan mempertimbangkan faktor-faktor seperti kualitas pelayanan dan harga. Kualitas pelayanan mencakup kemampuan perusahaan dalam memenuhi harapan pelanggan sementara harga mencerminkan nilai kepuasan seseorang terhadap produk yang dibelinya. Tujuan dari penelitian ini adalah untuk mengeksplorasi dampak dari kedua faktor tersebut dalam konteks keputusan pembelian di toko tersebut. Penelitian ini dilakukan pada populasi pelanggan Indomaret Camar Raya Kranggan, dengan melibatkan 90 responden yang mengisi kuesioner. Metode yang digunakan dalam peneitian ini adalah Accidental  sampling. Instrumen penelitian menggunakan skala Likert. Metode analisis statistik yang digunakan mencakup uji validitas, uji reliabilitas, uji asumsi klasik, korelasi, regresi linier berganda, koefisien determinasi, serta uji t dan uji F. Hasil dari penelitian ini menunjukan dari uji t yang menyatakan bahwa variabel kualitas pelayanan memengaruhi keputusan pembelian dengan nilai thitung sebesar 3,219 lebih besar dari ttabel (1.987) atau nilai signifikasi uji t sebesar 0,002 lebih kecil dari 0,05 (α=5%). Dan variabel harga berpengaruh positif terhadap keputusan pembelian dengan nilai thitung sebesar 3,784 lebih besar dari ttabel (1.987) atau nilai signifikasi uji t sebesar 0,002 lebih kecil dari 0,05 (α=5%).   The paper's abstract templates are used as a guide for writing paper for publications in journals Bina Sarana Informatika. The paper writers must follow the instructions given in this paper. Abstract is restricted from 100-250 words in Indonesian Language and English Language (in italics), should not contain equations, pictures, and table. The letter size for abstract, keywords, and body papers is 10 points using Times New Roman font. In the abstract they contain prologue of the raised problem, the proposed method and the desired results (hypothesis). The number of pages in the manuscript is at least 6 pages, a maximum of 12 pages using A4 paper size with 1 (single) spacing. This research aims to identify how service quality and price influence purchasing decisions at Indomaret Camar Raya Kranggan. Purchasing decisions are a process in which individuals choose the most appropriate behavior from several alternatives, taking into account factors such as service quality and price. Service quality includes the company's ability to meet customer expectations while price reflects a person's satisfaction with the product they buy. The aim of this research is to explore the impact of these two factors in the context of purchasing decisions at the store. This research was conducted on the customer population of Indomaret Camar Raya Kranggan, involving 90 respondents who filled out a questionnaire. The method used in this research is accidental sampling. The research instrument uses a Likert scale. The statistical analysis methods used include validity tests, reliability tests, classical assumption tests, correlation, multiple linear regression, coefficient of determination, as well as t tests and F tests. The results of this research show that the t test states that the service quality variable influences purchasing decisions with a t value of 3.219 which is greater than t table (1.987) or a t test significance value of 0.002 which is smaller than 0.05 (α=5%). And the price variable has a positive effect on purchasing decisions with a t value of 3.784 which is greater than t table (1.987) or a t test significance value of 0.002 which is smaller than 0.05 (α=5%).